Seragam Batik Sekolah Sebagai Pemicu Tawuran di Wilayah Sekolah Tingkat Atas X Kota Bogor - Naufal Fauzan; Triny Srihadiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The phenomenon of student brawls is a complex social issue that continues to occur across various regions in Indonesia, including in the city of Bogor, indicating that violence among adolescents remains a serious concern. One contributing factor to these conflicts is the use of school identity symbols, such as batik uniforms. Although batik uniforms are designed to represent cultural heritage and institutional identity, in practice, they are often interpreted by students as symbols of prestige and superiority. This study aims to answer the question, Why can school batik uniforms trigger student brawls. The research adopts a qualitative method with a case study approach. Data were collected through in-depth interviews with high school students from several schools in Bogor. The findings reveal that differences in batik designs particularly batik uniforms passed down from upperclassmen or alumni carry strong symbolic value in shaping group identity. When batik is used as a means of asserting dominance or becomes the object of ridicule (e.g., being taken or mocked by students from other schools), students tend to respond emotionally, which often escalates into physical conflict. Moreover, the collective tradition of “batikan,” in which students wear batik every Thursday, reinforces a strong sense of ownership and attachment to these symbols. Thus, while school batik uniforms were originally intended to promote cultural appreciation and unity, they can shift in meaning and function, becoming triggers for social conflict among students. Therefore, an educational and collaborative approach between schools is needed to foster a shared understanding that identity symbols should not divide, but rather unite.